Operations sustainability maturity model: preliminary findings of financial services in developing and developed countries. Issue 4 (20th November 2017) - Parker, David William; Loh, Alicia; Chevers, Delroy; Minto-Coy, Indianna; Zeppetella, Luca
Abstract : Purpose: This paper aims to develop and apply a measurement instrument to identify a comparative metric that identifies operational sustainability maturity across sectors and countries. Design/methodology/approach: Using structured interviews to complete the operations sustainability maturity model (OSMM) in financial services organisations, data were compared to show differences for developed and developing countries. Findings: The preliminary findings indicate that there is no significant difference in the sustainability maturity index between countries. However, size and profitability are strong indicators of sustainability maturity. Research limitations/implications: These findings represent preliminary findings drawn from the financial services sector in a limited number of countries. Expansion of the data set will give greater confidence of results. Practical implications: The OSMM is an empirical tool used to collect data that allows statistical evaluation of sustainable strategies used by firms in various sectors and in different countries. Social implications: Sustainability is of critical importance in the economic development of all countries. The OSMM embraces fiscal, operational and environmental considerations. The research gives new insights to alternative strategic imperatives. Originality/value: With increased awareness of organisational sustainability, academics have developed a number of tools, approaches and strategies to ensure commercial viability. However, few corporations have successfully institutionalised ongoing sustainability. OSMM is unique. Its wider application to embrace additional industry sectors and countries will bring new insight to strategic intent.